Utilising phytanic acid diastereomers for the characterisation of archaeological lipid residues in pottery samples. Issue 6 (10th February 2016) - Lucquin, Alexandre; Colonese, André C.; Farrell, Thomas F.G.; Craig, Oliver E.
Graphical abstract: Abstract: Phytanic acid diastereomers, 3 S, 7 R, 11 R, 15-phytanic acid ( SRR ) and 3 R, 7 R, 11 R, 15-phytanic acid ( RRR ), were determined by GC–MS in extracts of archaeological ceramic. The SRR % was higher in pottery from coastal sites corresponding with 13 C enriched n -alkanoic acid corroborating a predominantly marine origin for the food residues. Conversely, low SRR % and 13 C depleted n -alkanoic acid were found at inland sites, which are most likely derived from ruminant products. These observations are explained by differences in the bacterial transformation of phytol to phytanic acid between ruminant and aquatic organisms and allow these products to be easily distinguished in archaeological contexts.